The right to sexual identity:an analysis based on sentence 6040-2015-PA/TC of The Constitutional Court - Franciskovic Ingunza, Beatriz A. (2018)
The present jurisprudential comment describes a judgment of the Peruvian Constitutional Court regarding a case in which the violation of the Right of Identity of a transsexual is alleged. The analysis carried out by the Constitutional Court is relevant and decisive to face the situations of people who decide to change their sex and therefore their name. This sentence is the result of an analysis taking into account the social and cultural reality. In addition, it has also analyzed the two emblematic decisions regarding the change of sex previously processed.